Research perspectives in hydraulics and water resources engineering - Rama Prasad; Vedula, S. (World Scientific, 2002)
This book contains ten state-of-the-art review articles on selected topics in hydraulics/fluid mechanics and water resources engineering, written by alumni of the Indian Institute of Science who hold senior academic positions in reputable scientific institutions and who are active in research. The articles have all been peer-reviewed. At the end of each contribution, a rich list of references is given, encompassing most of the work done all over the world on the topic of the article. The topics are of current interest to research workers in many countries. Contents: Turbulen.